Water mass transformation in the Barents Sea inferred from radiogenic neodymium isotopes, rare earth elements and stable oxygen isotopes. - Makhotin, Mikhail; Ivanov, Vladimir (PANGAEA, 2018)
Boundary position of the Barents Sea between the North Atlantic and the Arctic basin causes a high degree of impact processes occurring in it and on the weather and climate in Northern Eurasia. The most important role in the formation of the hydrological regime of the sea plays warm and salty water incoming from the North Atlantic. The article examines the features of Atlantic water propagation in the Barents Sea based on a detailed hydrological survey and numerical simulation data with a high spatial resolution. Implementation of joint analysis confirmed several previously known features of water dynamics and thermohaline structure and clarified the nature of circulation and interaction of water masses in the little known north-eastern area of the Barents Sea.
Physical oceanography and inorganic nutrients in the Barents Sea from 2012-2014